When Christian education meets patriotism: Christian organisations’ response to the introduction of Moral and National Education in Hong Kong schools - Tse, Thomas Kwan-choi (British journal of religious education, 2017)
Plans by the Hong Kong Government to introduce moral and national education (MNE) as a compulsory subject in primary and secondary schools in 2010 encountered strong opposition. The controversy over the plans has lasted for two years, with the government and its supporters claiming that the subject will help to instil a stronger sense of national identity in children and critics deriding it as biased and constituting a form of brainwashing. The subject is also seen as posing troubles or a considerable threat to local Christian schools because most of them have had their own religious education programmes for years. Most Christian school-sponsoring bodies and parachurch organisations oppose the subject’s introduction, urging the government to scrap its curricular guidelines, and many say they will boycott its implementation. To bring the issues surrounding MNE into sharper focus, this article traces the development of Christian education in Hong Kong and analyses how local Christian communities perceive and have responded to the official proposal. Three prominent themes commonly emphasised in the Christian discourse are plural identities, conditional patriotism and universal values. These themes could shed light on wider theoretical discussion about the positive roles of religion and religious education for citizenship education.